Transformasi Pembelajaran melalui Pembuatan Media Ajar Berbasis Canva di SD Negeri Somoitan (JURNAL ILMIAH TUT WURI HANDAYANI, 2025)
The transformation of learning at Somoitan State Elementary School through Canva-based teaching media aims to improve the quality of learning and motivate students in the digital era. The use of Canva, an online graphic design platform, is integrated into a variety of subjects to create engaging and interactive materials, such as posters, and visual presentations. This research aims to improve the quality of teacher learning at Somoitan State Elementary School through creating and implementing Canva-based teaching media. The method used is qualitative research with a participatory observation approach, in-depth interviews and document analysis. The research subjects consisted of class I - VI teachers and students who were participants in the application of the teaching media. The research results show that the Canva-based teaching media creation training was successful in improving teachers' skills in designing and using more interesting and interactive media. The use of Canva-based teaching media in the classroom learning process has also been proven to increase student engagement significantly, with an increase in participation of 35% and an increase in the average student score from 72 to 85. In addition, teachers reported that using Canva helped them convey the material better. effective and efficient. However, this research also found challenges in implementation, such as technical problems related to internet connections and device limitations.